Protective effect of selenium on cisplatin induced nephrotoxicity: A double-blind controlled randomized clinical trial - Ali Ghorbani; Bita Omidvar; Abazar Parsi (Society of Diabetic Nephropathy Prevention, 2013)
Background: Renal injury is common following cisplatin infusion. Some agents have been used to attenuate cisplatin nephrotoxicity. However, except hydration, none of them has been proved to be effective. Objective: In this study selenium as an antioxidant supplement was tested on cisplatin induced renal injury. Patients and Methods: 122 cancerous patients (85 male and 37 female; age range of 14 to 82 years old) were enrolled to receive chemotherapy regimens consisting cisplatin. They were allocated into two groups using a random number list . Investigators, patients and analyzers all, were blinded in allocation by using sealed opaque envelopes. Intervention group received a single 400 mcg selenium tablet and patients in control group took a placebo tablet which was similar with selenium preparation in color, weight, shape and taste. Primary end points were an increase in plasma creatinine above 1.5 mg/dl in men and 1.4mg/dl in women, or increase of plasma creatinine more than 50% from baseline or urine flow rate less than 0.5 ml/kg/h. Creatinine level was measured initially and on the 5th day after cisplatin therapy. Results: There was no difference in cumulative dose of cisplatin between the groups (p=0.54). There were not evidences of acute renal failure (ARF) in cases. While, among placebo group, 7 patients had criteria of acute kidney injury. Conclusions: selenium could probably prevent cisplatin-induced acute kidney injury, when it is added to hydration therapy in cancerous patients.